Principles of neural sciences - Espinoza C., Sergio (Revista de Psicología, 1993)
Principles of neural sciences, 1991, Kandel, E.R., Schwartz, J.H. and Jessell, T.M., 3rd Edition, Prentice Hall International, Inc.